The association between dynamic changes in vitamin D and frailty alterations: A prospective analysis of UK Biobank participants - Pan Zhang; Jinghui Zhong; Xinfeng Liu; Wen Sun (Wiley, 2024)
Abstract Background Frailty is a common geriatric syndrome associated with reduced reserves and increased vulnerability to stressors among older adults. Vitamin D deficiency has been implicated in frailty, as it is essential for maintaining musculoskeletal functions. The relationship between dynamic changes in vitamin D levels and frailty over time has not been extensively studied. Methods This study utilized data from the UK Biobank. Baseline and longitudinal changes in vitamin D levels were measured. Frailty status was assessed using both the frailty phenotype and frailty index approaches and classified as robust, pre‐frail, or frail. Changes in frailty status were assessed by frailty phenotype at baseline (2006-2010) and the follow‐up (2012-2013). Mixed effect model was performed to examine the association between vitamin D levels and frailty status. Using multistate transition models, we assessed the impact of increasing vitamin D levels on the probabilities of transitioning between robust, pre‐frail, and frail states. Results Based on the frailty phenotype, 287 926 individuals (64.8%) were identified as having various degrees of frailty (median age 58.00 [51.00, 64.00] years, 55.9% females). Using the frailty index approach, 250 566 individuals (56%) were found to have different levels of frailty (median age 59.00 [51.00, 64.00] years, 55.3% females). Baseline vitamin D levels were found to be significantly associated with frailty status (frailty phenotype: ORfrail 0.78, 95% CI [0.76, 0.79], P < 0.001; frailty index: ORfrail 0.80, 95% CI [0.78, 0.81], P < 0.001). Dynamic changes in vitamin D levels were also found to be associated with changes in frailty over time. Furthermore, increasing vitamin D levels were associated with a transition from frailty to a healthier status. A higher degree of vitamin D (estimated at 1 nmol/L) was associated with a lower risk of transitioning from robust to prefrail (HR 0.997, 95% CI [0.995, 0.999]) and from prefrail to frail (HR 0.992, 95% CI [0.988, 0.995]). Conclusions This study highlights the importance of vitamin D in the context of frailty. Low vitamin D levels are associated with increased frailty risk, while increasing vitamin D levels may contribute to improving frailty status. Recognizing the relationship between vitamin D levels and frailty can inform personalized management and early interventions for frail individuals. Further research is needed to explore the potential effects of vitamin D interventions on frailty and deepen our understanding of the biological connections between vitamin D and frailty.